(untitled) (Research, Society and Development, 2020)
The pre-slaughter management of pigs, including loading, transport, unloading and resting time in the slaughterhouse can compromise animal welfare evidenced by the increased incidence of bodily injuries, skin lesions and compromised quality of carcasses and meat. The aim of this study was to assess whether the time taken to transport pigs from the production farm to the slaughterhouse influences on the bodily injuries and the skin damage score of carcasses. Transports lasting 2 hours, 8 hours and 14 hours were considered. Bruises, bite marks and abrasions were considered as bodily injuries. The incidence of injuries was high in the regions of the dorsum (76.53%), hind limbs (44.34%) and neck (38.97%) of the animals, but the transport time did not influence (P > 0.05) the incidence of bodily injuries, although there was a 16.28% reduction in the presence of injuries in the region of the rear limb in the shortest travel time (P = 0.0873). Abrasions on the dorsum were higher (P < 0.031) in transport lasting 8 hours, while the score for more severe injuries increased (P = 0.077) by an average of 77.06% in the longer transport compared to transport of 2 or 8 hours. The influence of transport time on the absence or severity of the skin damage in the carcass was evidenced by the Fisher test (P < 0.0001), allowing to infer that longer journeys contribute to the increase in carcasses with a worse skin damage in carcasses.